The effects of high-intensity physical exercise on the achievement of a 1,500-meter man running competition, maximal heart rate, and the development of personal tolerance - amara, samiha; Easa , Fahem (Journal of Physical Education, 2024)
Creating high-density workouts and determining how they affect the development of specific tolerance, maximum heart rate, and success in the 1,500-meter man run competition are the goals of the research. Therefore, the development of high-density physical exercises that arise during the run-off as a consequence of ongoing training and the utilization of exercise quality that satisfies the requirements of the 1,500-meter run-off competition are the primary goals of the research. Research is beset by a shortcoming in the competition's ability to achieve its unique tolerance and accomplishment skills, The 1,500-meter race amongst the elite men of the Iraqi Union of Forces for the Open Ages over 20 years of the 2023 sports season has been designated for the research community. The sample was split up by the 12 players into the six players, the command group, and the two pilot groups. The researchers came to the conclusion that men's 1,500-meter run competition achievement, maximum heart rate, and the development of special tolerance were all positively impacted by high-density physical training. In order to establish a unique tolerance for other competitions, the researchers advised high-density physical training. They also suggested conducting similar experiments and research in various age groups.